(untitled) (Bangladesh Journal of Botany, 2025)
Herbicides application increases residual effect in the soil which affect soil quality as well as crop productivity. Considering these facts, the present investigation was carried out with objectives to reduce the amount of herbicides in wheat production. Sorghum extract and herbicide are an integrated approach for weed management. The aim of the present study is to calibrate the potential of sorghum extract on weed suppression and yield of wheat as well as to reduce the use of quantity of herbicides. Sorghum extract (1:3) + ready-mix of clodinafop + metsulfuron 64 g/ha in T8 applied post-emergence significantly reduced the density of monocot weed (2.91, 2.36 and 1.88/m2), dicot weed (3.11, 2.36 and 1.99/m2) and significantly produced grain yield 4543 kg/ha and magnitude of enhancement were 34.87% over weedy check. The gross return (120351 Rs/ha), net return (87305 Rs/ha) and B-C ratio (3.64) were also obtained highest in T8. Bangladesh J. Bot. 54(2): 361-368, 2025 (June)